2021
DOI: 10.3390/ijms22084174
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Proteomics Reveals the Dynamic Regulation of the Tomato Proteome in Response to Phytophthora infestans

Abstract: Late blight (LB) disease is a major threat to potato and tomato production. It is caused by the hemibiotrophic pathogen, Phytophthora infestans. P. infestans can destroy all of the major organs in plants of susceptible crops and result in a total loss of productivity. At the early pathogenesis stage, this hemibiotrophic oomycete pathogen causes an asymptomatic biotrophic infection in hosts, which then progresses to a necrotrophic phase at the later infection stage. In this study, to examine how the tomato prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 95 publications
(114 reference statements)
0
9
0
Order By: Relevance
“…Within MF also ‘beta-glucosidase’ and ‘glucosidase activity’ terms were represented with four upregulated DEGs. Among them, Solyc01g059965.1.1 has been demonstrated to be implicated in the defense of tomato plants against pathogens ( Murata et al, 2019 ), and its expression has been found to be modulated in tomatoes upon infection with Cladosporium fulvum and Phytophthora infestans ( van Kan et al, 1992 ; Fan et al, 2021 ). Upregulation of Solyc06g073760.3.1 has been correlated to increased softening of transgenic tomato overexpressing a MADS-box transcription factor, affecting fruit development and ripening ( Huang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…Within MF also ‘beta-glucosidase’ and ‘glucosidase activity’ terms were represented with four upregulated DEGs. Among them, Solyc01g059965.1.1 has been demonstrated to be implicated in the defense of tomato plants against pathogens ( Murata et al, 2019 ), and its expression has been found to be modulated in tomatoes upon infection with Cladosporium fulvum and Phytophthora infestans ( van Kan et al, 1992 ; Fan et al, 2021 ). Upregulation of Solyc06g073760.3.1 has been correlated to increased softening of transgenic tomato overexpressing a MADS-box transcription factor, affecting fruit development and ripening ( Huang et al, 2017 ).…”
Section: Resultsmentioning
confidence: 99%
“…One pathogenesis-related (PR)-10 family protein salt tolerance homolog 2 (STH-2) was significantly induced at both transcription and protein levels during both PTI and ETI ( Figure 4C ). It was reported to be increased in tomato leaves in response to Phytophthora infestans ( Fan et al, 2021 ). Interestingly, phosphorylation of a conserved immunity regulator RPM1-interacting protein 4 (RIN4) ( Zhao et al, 2021 ) was significantly increased (e.g., Ser-144) during both PTI and ETI ( Supplementary Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…The significantly changed proteins belonged to immune response, redox processes, energy generation, and carbon fixation in the chloroplast. Fan et al [ 100 ] employed a DIA-MS method to study the interaction between tomato and the hemibiotrophic oomycete pathogen Phytophthora infestans . Among the changed proteins, several were involved in plant defense responses, metabolic pathways, and signaling.…”
Section: Ms Strategiesmentioning
confidence: 99%